Inhibition of cell proliferation in gastric cancer cell lines on exposure to rubriflordilactone A - Peng, Shang-Jin; Chen, Jue-Wei (Bangladesh Journal of Pharmacology, 2015)
The present study investigates the effect of rubriflordilactone A on the viability and its underlying mechanism in gastric cancer cell lines (SNU-1 and SNU-5) and normal gastric epithelial cell line (GES?1). Incubation of the gastric cancer and non cancer cell lines in acidic media led to reduction in the viability of the non cancer cells without any effect on cancer cells. Apoptosis in SNU-1 and SNU-5 cells was induced on exposure to rubriflordilactone A after 48 hours compared to the control cells (p<0.01). The percentage of apoptosis in SNU-1 and SNU-5 cells on exposure to rubriflordilactone A was 79.3 ± 4.7 and 74.0 ± 5.1, respectively after 48 hours. Exposure of SNU-1 and SNU-5 cancer cell lines to rubriflordilactone A at a concentration of 10 ?M in media with acidic pH decreased phosphorylation of ERK ½. The similar reduction was caused by ERK 1/2 phosphorylation inhibition, PD98059. Thus rubriflordilactone A reduces viability of gastric cancer cell lines by inducing apoptosis through the reduction of ERK 1/2 phosphorylation.